Kinerja Fly Ash terhadap Stabilisasi Tanah Lunak sebagai Material Perbaikan Tanah Dasar (Subgrade) - Wahyuni, Nanda Dwi; Putra, Andius Dasa; Syah, Aminudin; Iswan, Iswan (Universitas Lampung, 2021)
Subgrade has an important role in road construction work planning. However, a problem may appear because the soil which is used as the subgrade material has low quality, such as soft soil. One of the parameters to know the quality of the soil is by CBR testing and Atterberg Limit to know the index properties of soil that affect the quality. It is necessary to improve the subgrade soil through stabilization to produce construction materials based on standards by using additives in the form of fly ash. In this study, some variations of fly ash as a stabilization material are 0%, 5%, 10%, and 15% with curing time of 0 days, 7 days, and 14 days at room temperature. The results showed CBR value increased along with the increase in fly ash percentage as well as the length of curing time. The optimum CBR is 23.89% which is occurred in the addition of 15% fly ash with a 14-day curing time of at room temperature. The addition of fly ash percentage also affects the plasticity index of soils that have decreased from native soil by 28.19% to 9.02% in the addition of 15% fly ash. Key words : fly ash, soil stabilization, soft soil, CBR